Fatigue crack growth behavior and microstructural mechanisms in Ti-6Al-4V manufactured by laser engineered net shaping. (December 2016) - Zhai, Yuwei; Lados, Diana A.; Brown, Eric J.; Vigilante, Gregory N.
Highlights: Investigation of the fatigue crack growth behavior in LENS fabricated Ti-6Al-4V. Microstructural comparison in LENS low and high power fabricated Ti-6Al-4V. Correlation of fatigue crack growth behavior with characteristic microstructures. Examination of the influence of post-LENS annealing on mechanical properties. Establishment of the processing – microstructure – properties relationship. Abstract: Laser engineered net shaping (LENS) is an additive manufacturing technique developed specifically for fabricating metallic materials, such as steel, titanium alloys, and nickel-based superalloys, which are widely used in critical structural components. The layering procedure, cyclic heating, and fast cooling during LENS generate unique microstructural features and mechanical properties. Numerous research studies have been conducted mainly in areas including process-related simulation, microstructure characterization, and the performance of LENS fabricated materials under static loading conditions. The fatigue and fatigue crack growth properties and mechanisms in LENS materials, however, have not been thoroughly investigated. In this study, long fatigue crack growth tests were conducted at two stress ratios (R = 0.1 and 0.8) in Ti-6Al-4V fabricated utilizing different LENS processing parameters, in both as-fabricated and heat treated conditions. Microstructurally-small fatigue crack growth testing was also conducted. Both long and small fatigue crack growth mechanisms were established. Data and fundamental knowledge that facilitate the application of LENS in the design and repair of structural components were generated in this study and will be systematically discussed.